2022
DOI: 10.12973/eu-jer.11.2.763
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Gamification Principles into Higher Education

Abstract: <p style="text-align: justify;">The field of education was distinctly affected by the development of information and communication technologies, as they can make education more efficient, interactive, and available. Today’s students call for new innovative educational approaches. Digital communication technologies are the organic part of their life and they are group-oriented and experienced users of these technologies. Information and communication technologies must be used in a new and more interactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Los estudios demuestran resultados alentadores en las prácticas gamificadas en cursos de educación básica de inglés, en preparatoria de música y matemáticas, en pregrado de informática y derecho, en posgrado en varios cursos de tecnología educativa y en seminarios dirigidos a profesionales, en los cuales se ratifica el impacto de la gamificación en la motivación intrínseca, el espíritu de equipo, el aprendizaje sostenido. Resultados obtenidos en la escala de Likert muestran alta satisfacción de los estudiantes y se denotan pertinente formación de los docentes (Bovermann & Bastiaens, 2019;Carrión et al, 2021;Palová & Vejacka, 2022). En los estudios también se explora el contenido de la gamificación, la narrativa, las mecánicas y la retroalimentación.…”
Section: Resultsunclassified
“…Los estudios demuestran resultados alentadores en las prácticas gamificadas en cursos de educación básica de inglés, en preparatoria de música y matemáticas, en pregrado de informática y derecho, en posgrado en varios cursos de tecnología educativa y en seminarios dirigidos a profesionales, en los cuales se ratifica el impacto de la gamificación en la motivación intrínseca, el espíritu de equipo, el aprendizaje sostenido. Resultados obtenidos en la escala de Likert muestran alta satisfacción de los estudiantes y se denotan pertinente formación de los docentes (Bovermann & Bastiaens, 2019;Carrión et al, 2021;Palová & Vejacka, 2022). En los estudios también se explora el contenido de la gamificación, la narrativa, las mecánicas y la retroalimentación.…”
Section: Resultsunclassified
“…Another study showed that teachers' teaching practices also affect students' literacy competence. Teachers' teaching practices, such as the support provided by the teacher and positive feedback, are known to influence students' reading motivation (Guthrie, 2013;Hattie & Timperley, 2007;Narciss & Huth, 2004;Paľová & Vejačka, 2022). The teacher's teaching practice is known to influence the value of the students' pleasure reading index, both independently and together (Fahlevi, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Seeing the trend of Indonesia's PISA results from 2000 to 2018, it is necessary to immediately innovate in literacy learning. This might be difficult at first, because educational innovation is not a simple and easy process, including technological innovation with hands-on content and innovation in pedagogical approaches (Fu, 2020;Paľová & Vejačka, 2022;Youssef, 2012;Yuzulia, 2021). Most teachers in Indonesia still use the LOTS-type method, which needs to be innovated.…”
Section: Resultsmentioning
confidence: 99%
“…In digital learning environments, learners must self-organize and monitor their learning process. The idea in this context is that the game element in digital learning supports learners to engage in their learning activities more regularly to achieve higher learning outcomes with the various digital innovations available today (Paľová & Vejačka, 2022); (Schöbel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%